ANALISIS RASIO PROFITABILITAS DAN RASIO LIKUIDITAS UNTUK MENGUKUR KINERJA KEUANGAN PT HANJAYA MANDALA SAMPOERNA TBK - FEBRIANTI, FEBI; PRATIWI, ALIAH; WULANDARI, WULANDARI (GANEC SWARA, 2024)
The aim of this researcher is to analyze and explain financial performance in terms of Net Profit Margin (NPM), Return On Equity (ROE) , Current Ratio (CR) and Quick Ratio (QR) at PT. Hanjaya Mandala Sampoerna, Tbk, through financial report analysis will determine the company's ability to generate profits and determine the company's ability to fulfill its obligations and the results the company has achieved from its operational activities. The type of research carried out is descriptive research. The results of descriptive and statistical analysis showed that PT. Hanjaya Mandala Sampoerna, Tbk's Net Profit Margin (NPM) is in the bad category, this indicates that the company is less able to maximize the value of its profits. Return on Equity (ROE) is in the bad category. This indicates that the company has not been able to manage capital well and generate company profits. The Current Ratio (CR) is in the good category. This indicates that the company is able to pay short-term obligations or debts that are due. The Quick Ratio (QR) is in the good category. This indicates that the company is able to fulfill or pay current debt by taking into account the value of inventory